2014
DOI: 10.1371/journal.pone.0102286
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor Related Pathways Tested on an Endometrial Ex-Vivo Model

Abstract: IntroductionRecombinant human Granulocyte-Colony Stimulating Factor (rhG-CSF) supplementation seems to be a promising innovative therapy in reproductive medicine, used in case of recurrent miscarriage, embryo implantation failure or thin endometrium, although its mechanisms of action remain unknown. Our aim was to identify possible endometrial pathways influenced by rhG-CSF.Materials and MethodsHypothetical molecular interactions regulated by G-CSF were designed through a previous large scale endometrial micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
2
46
0
1
Order By: Relevance
“…The authors concluded that this cytokine could have an important function in achieving or maintaining pregnancy (Salmassi et al 2005). In another study, Rahmati and coworkers demonstrated significantly lower levels of GCSF receptors at the maternal-fetal interface in infertile women with implantation failure, and interestingly, stimulation with high-dose GCSF was able to increase the expression of GCSF receptors in these patients (Rahmati et al 2014). GCSF might affect reproduction, implantation, and pregnancy through several possible mechanisms; GCSF has been shown to induce the trophoblast proliferation, invasion, and maintenance during pregnancy (Miyama et al 1998, McCracken et al 1999.…”
Section: The Role Of Gcsf In Implantation and Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…The authors concluded that this cytokine could have an important function in achieving or maintaining pregnancy (Salmassi et al 2005). In another study, Rahmati and coworkers demonstrated significantly lower levels of GCSF receptors at the maternal-fetal interface in infertile women with implantation failure, and interestingly, stimulation with high-dose GCSF was able to increase the expression of GCSF receptors in these patients (Rahmati et al 2014). GCSF might affect reproduction, implantation, and pregnancy through several possible mechanisms; GCSF has been shown to induce the trophoblast proliferation, invasion, and maintenance during pregnancy (Miyama et al 1998, McCracken et al 1999.…”
Section: The Role Of Gcsf In Implantation and Pregnancymentioning
confidence: 98%
“…Many couples still remain unsuccessful after several IVF attempts causing deep effect on quality of life and a heavy financial burden (Zeyneloglu & Onalan 2014). With the recent advances in understanding the important role of granulocyte colony-stimulating factor (GCSF) in reproduction, and the detection of GCSF receptors in placental cytotrophoblasts, syncytiotrophoblasts, decidual stromal cells, endometrial gland cells, and follicular cells (Saito et al 1994, Miyama et al 1998, McCracken et al 1999, Salmassi et al 2005, Ledee et al 2008, Rahmati et al 2014, GCSF started to attract attentions in gynecology, especially in patients with recurrent abortions and/or infertility.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized trial endometrial injury resulted to a significant improvement (nearly development) in the implantation and clinical pregnancy and live birth rate (27.7%, 66.7% and 48.9% respectively) compared with control subjects who did not have endometrial biopsies (28,29). G-CSF administration appears to be associated with an increase in regulatory T cells and dendritic cells and appears to influence endometrial expression of genes which have cardinal role in implantation process (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…They also proliferate in response to granulocyte colony stimulating factor (G-CSF). Some have postulated that this action of G-CSF may reduce the incidence of miscarriage as they can recognize HLA-C on extravillous cytotrophoblasts [68][69][70]87].…”
Section: T Regulatory Cellsmentioning
confidence: 99%
“…This diagram gives a general overview. Estrogen, βHCG, and G-CSF are all known to induce expression of Treg cells and migration to the endometrium [68][69][70][71]. There they express IL-10, TGFβ, and TNFα [10].…”
Section: T-helper Lymphocyte-2 Cellsmentioning
confidence: 99%